Zamieszkiwać w bezdomności, czyli motyw domu w powieści Olgi Tokarczuk Dom dzienny, dom nocny - Viktória Vas (Postscriptum Polonistyczne)
Archetypal figures and themes inspired by myths have been present in Olga Tokarczuk’s prose from the beginning. The paper contains an interpretation of her early novel, House of Day, House of Night, and analyses the central theme of the text, that of home, to show the role of narrative creation in identity development.